2020
DOI: 10.1177/0312896220940762
|View full text |Cite
|
Sign up to set email alerts
|

Financial literacy and financial strategies: The mediating role of financial concerns

Abstract: This article analyses how the financial literacy of elderly people affects their decisions on the adoption of various financial strategies. Multiple mediator models with bootstrap techniques are used to identify the mediating mechanisms of financial concerns that transmit the effects of financial literacy onto specific financial strategies. We find (1) financial concerns mediate the majority of financial literacy-strategy nexuses; specifically, financially illiterate people are more likely to have financial co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 70 publications
(108 reference statements)
0
9
0
Order By: Relevance
“…However, for older women with a high level of education, covering the expenses of a nursing home is not an obstacle regarding the choice to receive care at a nursing home, thus creating a difference between men and women. In addition, compared with men, women’s financial literacy and financial security are relatively low ( Xue et al, 2019 , 2020 , 2021 ). When they have more income, they are more likely to spend for themselves rather than make other investments.…”
Section: Methodsmentioning
confidence: 99%
“…However, for older women with a high level of education, covering the expenses of a nursing home is not an obstacle regarding the choice to receive care at a nursing home, thus creating a difference between men and women. In addition, compared with men, women’s financial literacy and financial security are relatively low ( Xue et al, 2019 , 2020 , 2021 ). When they have more income, they are more likely to spend for themselves rather than make other investments.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it is concluded that college students in Tuxtepec, Oaxaca have low level of financial literacy which may affect their economic growth as they lack the ability to take financial risks and even make decisions regarding the acquisition of wealth. As pointed out by Xue, Gepp, O'Neill, Stern and Vanstone (2020), in their findings they identify that people with financial illiteracy are more likely to have financial worries, reduce their expenses, increase their debts and in some cases may even sell their homes.…”
Section: Discussionmentioning
confidence: 95%
“…The Item Response Theory (IRT) model estimates variables through an iterative computation process, making sufficient use of existing information. The IRT model also takes into account the difficulties of survey questions, making the estimations closer to real practice ( Xue et al, 2021 ). Therefore, we utilized the IRT model to measure business model design (BMD), including novelty-centered business model design (NBM) and efficiency-centered business model design (EBM).…”
Section: Methodsmentioning
confidence: 99%